Molecular Detection of Urogenital Schistosomiasis in Community Level in Semi-Rural Areas in South-East Gabon - Lady Charlène Kouna; Sandrine Lydie Oyegue-Liabagui; Chenis Nick Atiga; Chérone Nancy Mbani Mpega Ntigui; Roméo Karl Imboumy-Limoukou; Jean Claude Biteghe BI Essone; Steede Seinnat Ontoua; Diamella Nancy Moukodoum; Alain Prince Okouga; Jean Bernard Lekana-Douki (Diagnostics)
Background: Urogenital schistosomiasis is endemic in Gabon. Our study aimed to detect the prevalence of urinary schistosomiasis and to evaluate the diagnostic performance of the qPCR technique compared to microscopy for the detection of Schistosoma haematobium at the community level in a semi-rural area. Method: A cross-sectional survey was carried out. Urine samples were examined using Urine TICK test strips, a filtration technique, and qPCR. Schistosoma haematobium was detected by targeting the Dra1 gene. Results: The prevalence of urogenital schistosomiasis was determined and the performance of real-time PCR and urine strips was compared with that of urinary filtration. A total of 281 participants were enrolled in the study. The prevalence of urogenital schistosomiasis was increased slightly with the molecular technique (40.9%) compared to microscopy (36.7%), and the hematuria rate with Urine STICK was 33.5%. SAC (5–14 years old), Pre-SAC (>5 years old), and adolescents (15–17 years old) were the most affected group according to, respectively, whatever method was used. qPCR showed good agreement with microscopy, as well as excellent sensitivity (99.03%) and specificity (93.3). There was a good correlation between the number of eggs per 10 mL and the cycle threshold range. Conclusion: These results show the importance of using a combination of diagnostic tools in the surveillance of schistosomiasis, particularly in preschool children, adolescents, women of childbearing age, and chronic and asymptomatic cases.